Ovine platelet function is unaffected by extracorporeal membrane oxygenation within the first 24 h. Issue 7 (October 2015) - Hayes, Rylan A.; Foley, Samuel; Shekar, Kiran; Diab, Sara; Dunster, Kimble R.; McDonald, Charles; Fraser, John F.
Abstract : This study investigated platelet dysfunction during short-term extracorporeal membrane oxygenation (ECMO) and secondarily to determine if hyperoxaemia contributes to this dysfunction. Healthy sheep were anaesthetized and maintained on ECMO for either 2 or 24 h, with or without induction of smoke inhalation acute lung injury. A specialized animal-operating theatre was used to conduct the experimentation. Forty-three healthy female sheep were randomized into either a test or a control group. Following anaesthesia, test groups received ECMO ± smoke inhalation acute lung injury (SALI), whereas control groups were maintained with ventilation only ± SALI. Physiological, biochemical and coagulation data were obtained throughout via continuous monitoring and blood sampling. Platelet function was quantified through whole blood impedance aggregometry using Multiplate. Ovine platelet activity induced by adenosine diphosphate (ADP) and collagen was unaffected during the first 24 h of ECMO. However, progressive divergence of ADP-induced platelet activity was noted at cessation of the experiment. Pa O2 was inversely related to ADP-dependent platelet activity in the ECMO groups – a relationship not identified in the control groups. ADP and collagen-dependent platelet activity are not significantly affected within the first 24 h of ECMO in sheep. However, dysfunction in ADP-dependent platelet activity may have continued to develop if observed beyond 24 h. Hyperoxaemia during ECMO does appear to affect how platelets react to ADP and may contribute to this developing dysfunction. Long-term animal models and investigation in clinical animals are warranted to fully investigate platelet function during ECMO.